Long-term visual outcomes and histopathologic findings after cataract surgery in Ebola virus disease survivors in the Ebola virus RNA persistence in ocular tissues and fluids (EVICT) study. - Caleb D Hartley; Lucas Kim; Tolulope Fashina; Jack Begley; John G Mattia; Matthew J Vandy; Lloyd C Harrison-Williams; Jalikatu Mustapha; Robert F Garry; John S Schieffelin; Donald S Grant; Augustine Goba; et al. (PLoS Neglected Tropical Diseases)
Background/objectives Ebola virus disease (EVD) survivors develop post-acute ophthalmic sequelae, including a high prevalence of uveitis that may be complicated by vision-threatening cataract. After the non-detection of Ebola virus (EBOV) RNA in sampled ocular fluid, vision impairment due to cataract can be treated safely and effectively via manual small incision cataract surgery (MSICS). However, the long-term ocular visual outcomes and assessment of ocular tissues, including for genomic RNA, have been infrequently or not reported in Western African survivors. Subjects/methods A cohort of EVD survivors with visually significant cataract, in whom EBOV RNA was not detected by RT-PCR testing of ocular fluid sampled prior to MSICS, were followed for a year after intraocular lens replacement. Ophthalmic outcomes, including visual acuity (VA), adverse events, and follow-up examinations, were recorded. Ocular tissue specimens obtained at MSICS underwent histopathologic examination and in-situ hybridization (ISH) targeting EBOV genomic RNA. Results Thirty-four EVD survivors underwent MSICS and were included for analysis. The median age of EVD survivors who underwent surgery at enrollment was 22.5 years (Interquartile range, IQR: 16.5-33) and the cohort was comprised of 20 females (58.8%). Median logMAR VA at preoperative baseline was 3 (IQR: 1-3) which improved to 0.4 (IQR: 0-0.6; n = 10; p = 0.002) and 0.6 (IQR: 0.18-0.78; n = 18; p < 0.0001) at 6- and 12-months following surgery, respectively. EBOV RNA was not detected in 7 cataract and capsular tissue specimens obtained at the time of MSICS. Conclusions After MSICS, meaningful improvement in vision was maintained in EVD survivors at long-term follow-up. EBOV RNA was not detected in cataract and lens capsule specimens, providing additional reassurance of the low risk of EBOV RNA exposure during cataract surgery. Further study is needed to understand long-term ocular outcomes, including adverse events, in this population. Author summary Ebola virus disease (EVD) survivors may develop several ophthalmic sequelae including uveitis and cataract that may lead to severe vision loss if left untreated. Manual small incision cataract surgery (MSICS) has been utilized to treat cataract in EVD survivors with encouraging short-term outcomes, but the long-term visual acuity outcomes and the potential for Ebola virus RNA to reside in cataract material is unknown. In this study, we reported long-term visual acuity outcomes following MSICS in a cohort of EVD survivors along with histopathology findings from materials collected during surgery. Visual acuity improved over 12-month follow-up with encouraging safety measures. Ebola virus RNA was not detected in cataract and lens capsular tissue analyzed from EVD survivors. This study provides additional assurance regarding the safety and efficacy of cataract surgery, with potential for improved vision for EVD survivors.